Prespektif Siswa Terhadap Program Sekolah Adiwiyata Ditinjau dari Education for Sustainable Development di SMAN 1 Wirosari: Prespektif Siswa Terhadap Program Sekolah Adiwiyata Ditinjau dari Education for Sustainable Development di SMAN 1 Wirosari - Permata, Indah; Cahyani, Dwi Kurnia; Rukmi, Pramastuti Adiar; Roshayanti, Fenny (PendIPA Journal of Science Education, 2025)
This research aimed to analyze students' perspectives on the Adiwiyata school program at SMA Negeri 1 Wirosari within the framework of Education for Sustainable Development (ESD). The research sample consisted of 147 class X students selected using random sampling techniques. Data collection was carried out through surveys and analyzed based on four main aspects: natural resources, climate change, rural development, and disaster prevention and management. The research results showed that in the natural resources aspect, the value of the biology learning indicator was 71.90%, the extracurricular activities category indicator was 65.17%, and other activities was 69.96%. In the climate change aspect, the biology learning indicator obtained a score of 68.84%, the extracurricular activities category indicator was 57.41%, and other activities was 64.57%. In the rural development aspect, the biology learning indicator obtained a score of 50.61%, the extracurricular activities category indicator was 68.44%, and other activities was 76.49%. Meanwhile, in the aspect of disaster prevention and management, the biology learning indicator reached a value of 82.86%, the extracurricular activities category indicator was 76.39%, and other activities was 79.46%. These findings indicate that the Adiwiyata program has a positive contribution to the implementation of ESD principles at SMA Negeri 1 Wirosari, although there are variations in effectiveness in each aspect and indicator analyzed.